Thermodynamic efficiency of microbial growth is low but optimal for maximal growth rate - Westerhoff, Hans V. (1983)
Thermodynamic efficiency of microbial growth on substrates that are more oxidized than biomass approaches 24%. This is the theoretical value for a linear energy converter optimized for maximal output flow at optimal efficiency. For growth on substrates more reduced than biomass, thermodynamic efficiencies correspond to those predicted for optimization to maximal growth rate (or yield) only.